TAS-102 Plus Bevacizumab as an Effective and Well Tolerated Regimen in Chemotherapy-Refractory Advanced Colorectal Cancers – A Single Institution Retrospective Analysis - Joarder, Ritam; Patel, Dhwani; Tiwari, Atul; Choudhary, Jatin; Vana, Pranaya; Shenoy, Vallish; Mer, Neha; Ramaswamy, Anant; Bhargava, Prabhat; Ostwal, Vikas (South Asian Journal of Cancer, 2025)
There are limited data on the utility of TAS-102 plus bevacizumab in patients with chemotherapy-refractory metastatic colorectal cancer (mCRC) treated in India.Patients diagnosed with chemotherapy-refractory mCRC, defined as having received at least prior oxaliplatin and irinotecan–based chemotherapy between January 2017 and January 2022, and who began treatment with a combination of TAS-102 and bevacizumab were retrospectively analyzed for demographic variables, survivals, and prognostic parameters. The primary endpoint of the study was estimation of the median overall survival (OS) by the Kaplan–Meier method.The data of 143 patients satisfied the prespecified inclusion criteria and were included for analysis. There was a predominance of left-sided CRCs (78%) and patients having greater than two sites of distant metastases (87%), with 41% of patients with at least two lines of prior therapy. With a median follow-up of 11.6 months, the median OS of the entire cohort was 10.9 months, while the median progression-free survival was 4.4 months. The combination was well tolerated, with the most common grade 3/4 side effects being neutropenia (25%), anemia (6%), and thrombocytopenia (4%). Dose modifications in TAS-102 were required in 20% of patients, though this did not entail permanent cessation of TAS-102 in any patient. The presence of a resected primary was prognostic for improved OS (p < 0.001), while signet ring histology predicted inferior OS (p < 0.001).The combination of TAS-102 and bevacizumab is an efficacious and safe therapeutic option in patients with mCRC who have received at least two lines of prior systemic therapy. There were no requirements for cessation of the combination in the current study, underlying the well-tolerated nature of the combination.
Keywords: bevacizumab; chemotherapy-refractory colorectal cancer; TAS-102; tipiracil; trifluridine